Collaborative Governance Pada Platform Patrakomala sebagai Pengembangan Ekosistem Ekonomi Kreatif Kota Bandung - Cut Afni Tassya; Alya Zahra Rahayu; Yuni Siti Andini (Penerbit Jurnal Indonesia, 2025)
This research aims to find out how the role of the Culture and Tourism Office of Bandung City, especially the creative economy sector, collaborates in managing the creative economy. Bandung City, especially the creative economy sector, collaborates in managing the Patrakomala platform. Patrakomala platform, whose function is to facilitate multi-stakeholder collaboration to support the development of the creative economy ecosystem. to support the development of the creative economy ecosystem. As well as analyzing more deeply in depth, so that problems can be identified and can be resolved through making policy recommendations, in the process of using the Collaborative Governance approach based on the Morse & Stephens theory, (2012: 565-583) which has four indicators, namely 1) Assessment, 2) Initiation, 3) Deliberation, 4) Implementation. This research explains the process that interactions and shared norms between governance actors. governance actors. This theory aims to achieve the positive goals of each party. At the initiation stage, the development process begins with a collaborative approach, including collaborative approach, including the drafting of a creative economy roadmap, the enactment of regulations, and discussion forums such as the Patrakomala Coffee Club (PCC), a regulations, as well as discussion forums such as the Patrakomala Coffee Club (PCC) which involves creative economy actors in formulating inclusive programs. involving creative economy actors in formulating inclusive programs. stage deliberation stage emphasizes the importance of open dialogue between stakeholders to build consensus regarding the division of roles, allocation of resources, and development of sustainability strategies. development of sustainability strategies. Program implementation includes the development of Patrakomala Creative Center, incubation, exhibition, as well as competency improvement for creative economy creative economy actors, supported by mechanized